Using Economic Barometers to Analyze the Impact of the COVID-19 Pandemic on the National Economies - Puhachova М. V. (Statistics of Ukraine, 2020)
Bearing in mind a number of factors, well-known analytical companies and individual economists have been warning over a long time about the impending recession of the global economy. But the unexpected powerful impact on it from the pandemic can aggravate even the worst projections. Analysts are attempting to predict the economy development at global, regional and country level, in order to grasp and prevent future negative effects of the pandemic in all the spheres of human life. Now there exists a variety of qualitative indicators based on information from Business Tendency Survey and Consumer Sentiment Survey. Respectable international and national institutions use these indicators to quickly assess the current economic situation and predict its change for the several forthcoming quarters. These indicators are considered as very sensitive to any kind of events taking place in the economic and social life, because they are capable to provide the earliest signals of future change in the economy. The article contains a review of the dynamics of changes in the Global Economic Barometers computed and analyzed by well-known analytical institutions, and the barometers’ capacity to reflect the new pandemic’s impact on the global economy. The barometers provide up-to-date information about changes in the economy in the current month, with a strong lead over the official quantitative information. To estimate the pandemic’s impact on the development of Ukrainian economy, the author proposes to use Economic Sentiment Indicator and Business Confidence Indicators in the industry and the retail trade (for investigating the supply and demand), which are computed by the official statistics on the basis of qualitative information obtained from the surveys. These indicators are harmonized from the analogous European indicators, but issued with the quarter periodicity now. The conclusion is made about the urgent need to adopt the monthly periodicity for these and other barometers, created according to the European methodology, to enable for quick demonstration of the pandemic’s impact on the development of the Ukrainian economy. Also, it is proposed to search for new barometers that would be capable of providing for a more accurate reflection of change in the Ukrainian economy.